Variability of the Sea Surface Microlayer Across a Filament’s Edge and Potential Influences on Gas Exchange - Barthelmeß, Theresa; Schütte, Florian; Engel, Anja (Frontiers in Marine Science, 2021)
Major uncertainties in air-sea gas flux parameterizations may arise from a yet unpredictable sea surface microlayer (SML). Its influence on gas exchange is two-fold as organic matter, in particular surfactants, on one side and organisms enriched in the SML on the other can alter air-sea gas fluxes. However, spatial heterogeneity of the SML and its potential consequences for gas exchange are not well understood. This study examines the SML’s surfactant pool and the dynamics of microbial enrichment across the sharp hydrological front of a newly upwelled filament off Mauritania. The front was marked by a distinct decrease in temperature and salinity compared to the stratified water column outside the filament. Distinct chemical and microbial SML properties were observed and associated with the filament. Overall, organic matter in the SML was significantly higher concentrated inside the filament and in equivalence to the underlying water. Degradation indices derived from total amino acids (TAA) composition indicated production of fresh organic matter inside and increased degradation outside the filament. Moreover, a shift in the microbial community was observed, for instance Synechococcus spp. prevailed outside the filament. Autotrophic and heterotrophic microorganisms preferably colonized the SML outside the filament. Organic matter enrichment in the SML depended largely on the chemical nature of biomolecules. Total organic carbon (TOC), total nitrogen and total combined carbohydrates were only slightly enriched while glucose, TAA and surfactants were considerably enriched in the SML. Surfactant concentration was positively correlated to TAA, in particular to arginine and glutamic acid, indicating that fresh organic matter components enhanced surface activity. Further, TOC and surfactant concentration correlated significantly (r2 = 0.47, p-value < 0.001). The lower limit of this linear correlation hits approximately the lowest TOC concentration expected within the global surface ocean. This suggests that surfactants are primarily derived from autochthonous production and most refractory components are excluded. Using a previously established relationship between surfactants and CO2 gas exchange (Pereira et al. 2018), we estimated that surfactants suppressed gas exchange by 12% inside the filament. This could be of relevance for freshly upwelled filaments, which are often supersaturated in greenhouse gases.